2022
DOI: 10.1136/jitc-2022-005060
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of90Y-NM600 targeted radionuclide therapy and PD-1 blockade is limited by regulatory T cells in murine prostate tumors

Abstract: BackgroundSystemic radiation treatments that preferentially irradiate cancer cells over normal tissue, known as targeted radionuclide therapy (TRT), have shown significant potential for treating metastatic prostate cancer. Preclinical studies have demonstrated the ability of external beam radiation therapy (EBRT) to sensitize tumors to T cell checkpoint blockade. Combining TRT approaches with immunotherapy may be more feasible than combining with EBRT to treat widely metastatic disease, however the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Surprisingly, 225 Ac-NM600 combined with anti-PD1 had no effects on anti-tumor responses compared to 225 Ac-NM600 + isotype control or 225 Ac-NM600 alone, most likely because CD8+ cells were also depleted in that group. These results are in accordance with our recently published studies demonstrating that 90 Y-NM600 RPT with anti-PD-1 ICI had no benefits over RPT alone in these models unless Tregs were simultaneously depleted ( 20 ). While these preliminary results showed that, under the tested conditions, the addition of anti-PD1 to 225 Ac-NM600 did not enhance therapeutic effects, further optimization of this combined regimen may uncover synergies between the two therapeutic modalities.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Surprisingly, 225 Ac-NM600 combined with anti-PD1 had no effects on anti-tumor responses compared to 225 Ac-NM600 + isotype control or 225 Ac-NM600 alone, most likely because CD8+ cells were also depleted in that group. These results are in accordance with our recently published studies demonstrating that 90 Y-NM600 RPT with anti-PD-1 ICI had no benefits over RPT alone in these models unless Tregs were simultaneously depleted ( 20 ). While these preliminary results showed that, under the tested conditions, the addition of anti-PD1 to 225 Ac-NM600 did not enhance therapeutic effects, further optimization of this combined regimen may uncover synergies between the two therapeutic modalities.…”
Section: Discussionsupporting
confidence: 93%
“…Serial histological examination of potential organs at risk of radiotoxicity, such as the heart, liver, spleen, and kidney, revealed no signs of acute cellular toxicity. In addition, via CBC analysis, we identified mild bone marrow toxicity with dose-dependent cytopenia on early time points which were confirmed through histology of bone marrow; however, these were resolved by day 28, similar to our previous findings ( 2022 ). Functional kidneys and liver metabolic assays further confirmed 177 Lu-NM600 and 225 Ac-NM600’s tolerability, with no clinically relevant effects on blood chemistries at any of the IA or time points investigated.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations